Prevalence of Transfusion Transmitted Infections from Eastern Part of India: A 5-Year Experience - Bhutia, Chumila Thinley; Das, Deepak (Annals of Pathology and Laboratory Medicine, 2019)
Background: Blood transfusion saves millions of lives everyday across the world. However, transmission of infections along with blood transfusion though can be minimized but cannot be completely avoided. The chance of transmitting infections is higher in underdeveloped laboratories with limited resources. Transfusion transmitted infections (TTI’s) can cause significant morbidity and mortality as well. Methods: A retrospective data analysis was carried out in SMIMS, Gangtok, in the far eastern part of India to estimate the incidence of transfusion transmitted infections (TTI’s) in the last five years, from January, 2013 to December, 2017. 5 ml of venous blood was collected from each donor and blood was screened for HBsAg, HIV, HCV, Syphilis and Malaria using card tests. The reactive cases were confirmed with third generation ELISA, TrueLISATM. Result: A total of 10,011 blood donors were screened from January, 2013 to December, 2017. Male voluntary donors were more compared to female donors. Among the 135 seropositive cases 92 donors (0.91%) were positive for HBsAg, 23 donors (0.22%) were positive for anti HCV, 16 donors (0.15%) were positive for HIV while 4 donors(0.04%) were positive for syphilis. No case of malaria was noted in our study. The overall prevalence of HBsAg, HCV, HIV and syphilis was 0.91%, 0.15%, 0.22%, and 0.04% respectively. Conclusion: The goal of routine blood transfusion should be to decrease the seroprevalance of TTI’s. Strict blood donor selection and proper screening methods along with nucleic acid detection can help in reducing the seroprevalance of TTI’s.